Beamforming performance assessment for QAM and OFDM modulation schemes in MIMO wireless systems - Estupiñán Calderón, Darío Alejandro (2020)
Fixed Wireless Access (FWA) arrives as an alternative to Fiber to the Home services thanks to new 5G cellular networks. It is one of the alternatives for the services offered in the new Integrated Access and Backhaul architecture. These point-to-point links take place generally from a multiple-antenna base station to a single-antenna customer premise equipment in a quasi-static wireless channel. We perform link level simulations with a complete Tx and Rx signal processing chain, to evaluate the performance of OFDM and single carrier QAM in mmWave channels using QUADRIGA. Results from LOS, NLOS, urban, suburban channels and the impact of element malfunctioning in 2D antenna-array transmitters are evaluated.